Family planning adoption and unmet needs: Spousal agreement in rural Varanasi - Neeti Purwar; Hari Shankar; Kalpana Kumari (Wolters Kluwer Medknow Publications, 2018)
Background: There have been very few studies in India where both partners' involvement in family planning is seen. The present study was undertaken to assess the spousal agreement level regarding family planning adoption and unmet needs. Materials and Methods: Married couples where wife was in reproductive age group (15-44 years) were included. A pretested, semi-structured interview schedule was used for the study. Sterilized couples were excluded. Interview of both husband and wife was done on the same day but in isolation. Results: There was excellent to poor agreement was reported among husbands and wives in fertility desire (κ = 0.769), current use of contraception (κ = 0.581), unmet need for family planning (κ = 0.416), ideal family size (Spearman correlation = 0.329), and approval for the use of contraception (κ = 0.300). In 6.1% of cases, husband-only unmet need was reported. Conclusion: There is need to encourage spousal communication so that they can make informed decisions on contraceptive choice. Husband-only unmet need for family planning was found, so man may be a potential entry point of national demographic health surveys to improve the contraceptive usage among couples and reduce the unmet need of them.